Pengkomposan Sisa Taman Menggunakan Kaedah Timbunan Statik Berudara Dan Deram Berputar - Sabiani, Nor Habsah Md. (2008)
The present work studied the composting of yard waste from Pulau Burung Sanitary In this Landfill. study, the two methods of composting that were analyzed are aerated static pile (ASP) and rotary drum (RD). In the ASP method, aeration was carried out both mechanically by an air blower and by manual turning. While in the RD method, air was supplied by manual turning (rotation). Yard waste (YW) and cow manure (CM) were used as substrates. The study was divided into three stages i.e Stage I to III. Stage I involved the study to determine the physical and chemical characterization of yard waste such as weight, composition, size distribution, bulk density, moisture content, pH, C:N ratio, nutrient and heavy metal content.